(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article analyzes the historical and cultural regions through which the trade routes of Central Asian settled oases passed, particularly focusing on how Sogdiana’s routes connected the East, West, North, and South, integrating the entire region into transcontinental networks. It examines the movement of trade caravans and diplomatic missions originating from Samarkand (Sogdiana) along the Chach, Fergana, and Semirechye (Yettisuv) routes, as well as their integration of representatives from Ustrushana into their ranks.